Design and analysis of temperature-variation-tolerant ultra-low voltage circuits for wireless sensor nodes - Phua, Isabel Jie Wei (2014)
Memory arrays are an essential building block in any digital system. SRAM is a device that has infiltrate into myriads of hardware systems, acting as an important component. The designing of an SRAM is very critical to designing other digital circuits as well. Memory dominates the majority of space in an integrated circuit. SRAM design comprises of prime considerations such as improved speed and condensed layout area.